The contributions of neuropsicopedagogy in the art of learning and teaching with emphasis in dyslexia (Research, Society and Development, 2021)
Reflections are presented on the relevance of the role of the neuropsychopedagogist in the teaching and learning process in the institutional school environment, with an emphasis on learners with dyslexia and its comorbidities. Neuropsychopedagogy effectively contributes to the process of affective interrelationship, thus being able to mediate the process of teaching and learning based on neurolearning. This work is a qualitative research, through a descriptive and bibliographical study, based on theorists who study the subject, among others that contemplate the theme. The discussion does not emphasize the neuropsychopedagogist, as the solver of the problems, therefore, it is necessary to resort to research and constitutional summaries, but also to recognize the presence of this professional in the school institution, in which his position must be based on bonds of affection, valuing dialogue, ethics and science. Neuropsychopedagogy will bring successful contributions to mediate, promote, intervene and stimulate the construction of knowledge, supported by studies on neuroplasticity, stimulating and motivating adequate opportunities for learning. The multidisciplinary vision of the neuropsychopedagogist can be exercised with dedication to the success of the specificities presented, valuing the entire context and educational policies, with the mission of promoting harmonious harmony in daily school life and in life beyond the school walls, providing opportunities for significant learning and brain relationships and the unique behavior of each individual dyslexic or not.